5 - from which we obtain E X | A = Z 3 2 x 2 x 5 dx = 2 x 3 15 ⎩ ⎩ ⎩ 3 2 = 54 15 − 16 15 = 38 15(b We have E Y = E X 2 = Z 3 1 x 3 4 dx =

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: from which we obtain E [ X | A ] = Z 3 2 x · 2 x 5 dx = 2 x 3 15 ⎩ ⎩ ⎩ 3 2 = 54 15 − 16 15 = 38 15 . (b) We have E [ Y ] = E [ X 2 ] = Z 3 1 x 3 4 dx = 5 , and E [ Y 2 ] = E [ X 4 ] = Z 3 1 x 5 4 dx = 91 3 . Thus, var( Y ) = E [ Y 2 ] − ( E [ Y ] ) 2 = 91 3 − 5 2 = 16 3 . Solution to Problem 3.19. (a) We have, using the normalization property, Z 2 1 cx − 2 dx = 1 , or c = 1 Z 2 1 x − 2 dx = 2 . (b) We have P ( A ) = Z 2 1 . 5 2 x − 2 dx = 1 3 , and f X | A ( x | A ) = 6 x − 2 , if 1 . 5 < x ≤ 2, , otherwise. (c) We have E [ Y | A ] = E [ X 2 | A ] = Z 2 1 . 5 6 x − 2 x 2 dx = 3 , E [ Y 2 | A ] = E [ X 4 | A ] = Z 2 1 . 5 6 x − 2 x 4 dx = 37 4 , and var( Y | A ) = 37 4 − 3 2 = 1 4 . Solution to Problem 3.20. The expected value in question is E [Time] = ( 5 + E [stay of 2nd student] ) · P (1st stays no more than 5 minutes) + ( E [stay of 1st | stay of 1st ≥ 5] + E [stay of 2nd] ) · P (1st stays more than 5 minutes) . 41 We have E [stay of 2nd student] = 30, and, using the memorylessness property of the exponential distribution, E [stay of 1st | stay of 1st ≥ 5] = 5 + E [stay of 1st] = 35 . Also P (1st student stays no more than 5 minutes) = 1 − e − 5 / 30 , P (1st student stays more than 5 minutes) = e − 5 / 30 . By substitution we obtain E [Time] = (5 + 30) · (1 − e − 5 / 30 ) + (35 + 30) · e − 5 / 30 = 35 + 30 · e − 5 / 30 = 60 . 394 . Solution to Problem 3.21. (a) We have f Y ( y ) = 1 /l , for 0 ≤ y ≤ l . Furthermore, given the value y of Y , the random variable X is uniform in the interval [0 , y ]. Therefore, f X | Y ( x | y ) = 1 /y , for 0 ≤ x ≤ y . We conclude that f X,Y ( x, y ) = f Y ( y ) f X | Y ( x | y ) = ( 1 l · 1 y , ≤ x ≤ y ≤ l , , otherwise. (b) We have f X ( x ) = Z f X,Y ( x, y ) dy = Z l x 1 ly dy = 1 l ln( l/x ) , ≤ x ≤ l. (c) We have E [ X ] = Z l xf X ( x ) dx = Z l x l ln( l/x ) dx = l 4 . (d) The fraction Y /l of the stick that is left after the first break, and the further fraction X/Y of the stick that is left after the second break are independent. Furthermore, the random variables Y and X/Y are uniformly distributed over the sets [0 , l ] and [0 , 1], respectively, so that E [ Y ] = l/ 2 and E [ X/Y ] = 1 / 2. Thus, E [ X ] = E [ Y ] E h X Y i = l 2 · 1 2 = l 4 . Solution to Problem 3.22. Define coordinates such that the stick extends from position 0 (the left end) to position 1 (the right end). Denote the position of the first break by X and the position of the second break by Y . With method (ii), we have X < Y . With methods (i) and (iii), we assume that X < Y and we later account for the case Y < X by using symmetry. Under the assumption X < Y , the three pieces have lengths X , Y − X , and 1 − Y . In order that they form a triangle, the sum of the lengths of any two pieces must exceed the length of the third piece. Thus they form a triangle if X < ( Y − X ) + (1 − Y ) , ( Y − X ) < X + (1 − Y ) , (1 − Y ) < X + ( Y − X ) ....
View Full Document

This note was uploaded on 01/11/2011 for the course MATH 170 taught by Professor Staff during the Spring '08 term at UCLA.

Page1 / 10

5 - from which we obtain E X | A = Z 3 2 x 2 x 5 dx = 2 x 3 15 ⎩ ⎩ ⎩ 3 2 = 54 15 − 16 15 = 38 15(b We have E Y = E X 2 = Z 3 1 x 3 4 dx =

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online